Titanium-based silicide quantum dot superlattices for thermoelectrics applications. (18th June 2015) - Savelli, Guillaume; Silveira Stein, Sergio; Bernard-Granger, Guillaume; Faucherand, Pascal; Montès, Laurent; Dilhaire, Stefan; Pernot, Gilles
Abstract: Ti-based silicide quantum dot superlattices (QDSLs) are grown by reduced-pressure chemical vapor deposition. They are made of titanium-based silicide nanodots scattered in an n -doped SiGe matrix. This is the first time that such nanostructured materials have been grown in both monocrystalline and polycrystalline QDSLs. We studied their crystallographic structures and chemical properties, as well as the size and the density of the quantum dots. The thermoelectric properties of the QDSLs are measured and compared to equivalent SiGe thin films to evaluate the influence of the nanodots. Our studies revealed an increase in their thermoelectric properties—specifically, up to a trifold increase in the power factor, with a decrease in the thermal conductivity—making them very good candidates for further thermoelectric applications in cooling or energy-harvesting fields.